Assessing some economic and biological characters of introduced varieties of genus Astilbe Buch.-Ham ex D.Don - Ю. В. Буйдін (Plant Varieties Studying and Protection)
Purpose. To study flowering productivity and reproductive ability of multiple-aged plants of introduced Astilba varieties, assess varieties for these characters and investigate the effectiveness of vegetative propagation. Methods. Field experiment, introduction and statistics evaluation. Results. The analysis of published data and author’s own observations revealed that Astilba varieties are highly tolerant for winter and frost conditions as well as pest and disease resistant, therefore we defined flowering productivity and reproductive ability as main economic and biological characters that are subject to assessment. According to the results of flowering efficiency study, it was found that the highest value of this index for the most studied varieties was observed on the fourth year of cultivation. Whereas the majority of varieties rating was relatively low, Astilbe flowering productivity on the whole was sufficiently high. In order to arrange collection plots, flower beds and implement the selection process, the most effective method of vegetative propagation can be used – the division of rhizomes into pieces with three to five renovation buds, and for mass reproduction – with one or two buds. It turned out that for Astilbe the indicator of reproductive ability is specific. For most of the investigated five-year varieties it was quite high. We have noted a high positive correlation between the index of reproductive ability and flowering productivity. Varieties with optimal flowering had high value of planting material yield. Conclusions. Based on the experimental data, the flowering productivity and reproductive ability of multiple- aged plants of Astilbe introduced varieties was studied, varieties was assessed according to these characters, and the effectiveness of vegetative propagation was investigated.